2018
DOI: 10.1101/470153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Premovement suppression of corticospinal excitability may be a necessary part of movement preparation

Abstract: In a warned reaction time (RT) task, corticospinal excitability (CSE) decreases in taskrelated muscles at the time of the imperative signal (preparatory inhibition). Because RT tasks emphasise speed of response, it is impossible to distinguish whether preparatory inhibition reflects a mechanism preventing premature reactions, or whether it is an inherent part of movement preparation. We used transcranial magnetic stimulation (TMS) to study CSE changes preceding RT movements and movements that were either se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(63 reference statements)
2
8
1
Order By: Relevance
“…Finally, single-pulse TMS using 1mV WS intensity at RT-200 resulted in significantly smaller MEP amplitudes than at WS (t ¼ 3.916, p ¼ 0.001), confirming that corticospinal excitability decreased during movement preparation (Fig. 1D) [16].…”
Section: Resultssupporting
confidence: 54%
“…Finally, single-pulse TMS using 1mV WS intensity at RT-200 resulted in significantly smaller MEP amplitudes than at WS (t ¼ 3.916, p ¼ 0.001), confirming that corticospinal excitability decreased during movement preparation (Fig. 1D) [16].…”
Section: Resultssupporting
confidence: 54%
“…The results we present here, and previous findings that preparatory inhibition is present before self‐timed movements (Ibáñez et al . 2020), are then inconsistent with the impulse control hypothesis (Duque & Ivry, 2009; Duque et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2011; Ibáñez et al . 2020). There are three main explanations which have been put forward regarding the role of this suppression of motor circuits before movement onset.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first TMS experiment applied in this context showed that cortical excitability is reduced during movement preparation (Hasbrouq et al 1997 ). While this was initially interpreted as an inhibitory signal that helps to prevent actions from being executed prematurely (Duque and Ivry 2009 ), the preparatory suppression effect is still a matter of debate (Ibáñez et al 2019b ).…”
Section: Introductionmentioning
confidence: 99%